Minimally important differences for interpreting the EORTC QLQ‐C30 in patients with advanced colorectal cancer treated with chemotherapy. (28th August 2020) - Musoro, J. Z.; Sodergren, S. C.; Coens, C.; Pochesci, A.; Terada, M.; King, M. T.; Sprangers, M. A. G.; Groenvold, M.; Cocks, K.; Velikova, G.; Flechtner, H.‐H.; Bottomley, A.; et al.
Abstract: Aim: The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ‐C30) assesses the health‐related quality of life of patients in cancer trials. There are currently no minimally important difference (MID) guidelines for the EORTC QLQ‐C30 for colorectal cancer (CRC). This study aims to estimate MIDs for the EORTC QLQ‐C30 scales in patients with advanced CRC treated with chemotherapy and enrolled in clinical trials. Method: The data were obtained from three published EORTC trials that treated CRC patients using chemotherapy. Potential anchors were selected from clinical variables based on their correlation with EORTC QLQ‐C30 scales. Anchor‐based MIDs for within‐group change and between‐group change were estimated via the mean change method and linear regression, respectively, and summarized using weighted correlation. Distribution‐based MIDs were also examined. Results: Anchor‐based MIDs were determined for deterioration in 8 of the 14 EORTC QLQ‐C30 scales and in 9 scales for improvement, and varied by scale, direction of change and anchor. MIDs for improvement (deterioration) ranged from 6 to 18 (−11 to −5) points for within‐group change and 5 to 15 (−10 to −4) for between‐group change. Summarized MIDs (in absolute values) per scale mostly ranged from 5 to 10 points. Conclusions: These findings have clinical relevance for the interpretation of treatment efficacy and the design of clinical trials by informing sample size requirements.